2012
DOI: 10.1007/s00167-012-2293-y
|View full text |Cite
|
Sign up to set email alerts
|

Patella infera or patellar tendon adherence after high tibial osteotomy

Abstract: The shortening of the tendon occurs as a result of adherence in the distal part of the tendon. It would appear that it is this shortening that causes the difficulties encountered during arthroplasty surgery of osteotomy patients, and not patella infera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In terms of the change in the sagittal alignment of patella after HTO, it has variable chances to change the patella height, which was confirmed in previous studies. 2,4,9,[14][15][16][17]27,30 However, the extent of the change could be different between various indexes of patellar height. [31][32][33] To interpret the results of sagittal alignment of patella correctly, it is essential to consider whether the indexes are sufficiently representative of the patellar height before and after HTO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the change in the sagittal alignment of patella after HTO, it has variable chances to change the patella height, which was confirmed in previous studies. 2,4,9,[14][15][16][17]27,30 However, the extent of the change could be different between various indexes of patellar height. [31][32][33] To interpret the results of sagittal alignment of patella correctly, it is essential to consider whether the indexes are sufficiently representative of the patellar height before and after HTO.…”
Section: Discussionmentioning
confidence: 99%
“…Four comparative studies showed the patellar height after both OW and CW HTO. 5,10,14,20 A total of 11 studies [2][3][4]9,15,16,[21][22][23][24][25] reported postoperative changes in patellar height or patellofemoral alignment only after OW HTO and five studies [26][27][28][29][30] reported changes only after CW HTO. The measured indexes used for the evaluation of patellar indexes in each study are shown in ►Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…26 Tendon stiffness may affect future surgical planning for total knee arthroplasty and may necessitate proximal quadriceps-plasty or distal tendino-osseous release. 13 This study had several limitations. The sample size was too small for correlation analysis or validation of the SWE.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the patellofemoral joint on the sagittal plane is also in uenced by the operation [2] . Several studies have shown that OWHTO causes patella infra, increases patellofemoral joint pressure pain, increases the risk of patellofemoral OA progression, and makes it more di cult for total knee arthroplasty to be performed in the future [3][4][5][6][7][8] . Kim et al [8] reported the prevalence of the progression of patellofemoral OA to be 41.2% in the femoral trochlea and 21.9% in the patella articular surface after more than 2 years in 114 patients who underwent OWHTO.…”
Section: Introductionmentioning
confidence: 99%
“…Patella infra and patellofemoral malalignment have been reported to result from tibial tuberosity distalization and patellar tendon adherence [7,9] . To prevent patella infera, several studies have reported that osteotomy in the distal tibial tuberosity or below the tuberosity should be performed [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%